Cold Regions Engineering 2012 2012
DOI: 10.1061/9780784412473.075
|View full text |Cite
|
Sign up to set email alerts
|

Penetration Rate-Controlled Electrical Resistivity and Temperature Piezocone Penetration Tests in Warm Ice-Rich Permafrost in Northern Quebec, Canada

Abstract: Electrical resistivity and temperature piezocone penetration test (RTCPTU) was carried out in warm ice-rich permafrost formed in silty soil near Umiujaq, Northern Quebec, Canada, to study the cryostratigraphy of permafrost and adapt soil classification charts for the interpretation of RTCPTU in such environment. A linear pushing system based on an actuator technology was used to accurately control the penetration rate of the piezocone in permafrost.According to the interpretation of the RTCPTU logs, cryostrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The ice content of the permafrost mounds varies between 40% and 90% (R. Fortier et al., 1994, 2008), while the unfrozen water content values average around 10% where ground temperature is lowest at −2°C (LeBlanc et al., 2004). The permafrost temperature is close to 0°C and generally varies between −0.1 and −2°C depending on the depth (R. Fortier et al., 2008; R. Fortier & Yu, 2012; LeBlanc et al., 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ice content of the permafrost mounds varies between 40% and 90% (R. Fortier et al., 1994, 2008), while the unfrozen water content values average around 10% where ground temperature is lowest at −2°C (LeBlanc et al., 2004). The permafrost temperature is close to 0°C and generally varies between −0.1 and −2°C depending on the depth (R. Fortier et al., 2008; R. Fortier & Yu, 2012; LeBlanc et al., 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Due to frost heave and the accumulation of segregated ice lenses, permafrost in the valley exists in the form of raised periglacial landforms, or permafrost mounds, sometimes called lithalsas (Allard et al., 1986; Allard & Seguin, 1987; Harris, 1993). Previous studies carried out at several permafrost mounds located in the Tasiapik Valley focused on permafrost cryostratigraphy by conducting electrical resistivity and temperature piezocone penetration tests (R. Fortier & Yu, 2012). Results revealed that the stratified cryostructure consists of a complex reticulated sequence of centimetric ice lenses and frozen soil layers (fine sediments or sand beds) (Calmels & Allard, 2008; R. Fortier et al., 2008; R. Fortier & Yu, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical permafrost thickness in the Tasiapik Valley varies from about 4 m for small permafrost mounds to in excess of 25 m for permafrost plateau ( Fig. 6b; El Baroudi and Fortier 2014;Fortier and Yu 2012). The active layer, the surficial layer affected by freeze-thaw cycles, is from 1.5 to 2 m thick where the silty sand unit outcrops in the lower valley.…”
Section: Permafrost Aggradation and Degradationmentioning
confidence: 99%
“…5 and 6b), and the results from the geophysical investigation (Figs. 6, 7, and 8), along with other sources of information including cone penetration tests and other geophysical investigations (Buteau et al 2005; El Baroudi and Fortier 2014;Fortier and Yu 2012;LeBlanc et al 2004;LeBlanc et al 2006), were used to build a 3D geological model of the studied watershed in the Tasiapik Valley (Fig. 9).…”
Section: Three-dimensional Geological Modelling Of the Watershedmentioning
confidence: 99%